The Notion of Money Illusion and Its Development in Economics - Košková, Dominika; Potužák, Pavel; Mirvald, Michal; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
This thesis maps development of money illusion through the history of economic thought and analyzes relevance of the concept in these days. The story begins in 1928 with Irving Fisher, who saw money illusion as a failure to perceive changes in purchasing power of money. Different notion was developed by John Maynard Keynes when he proposed a non-homogeneous labor supply. In the 1970s, the success of rational expectations theory led to a dismissal of the original theories of money illusion and Tobin's critique revealed also an inconsistency of the Keynesian notion. Since then, money illusion lost its position in the mainstream economic science. The modern theories were, however, able to align money illusion with rational expectations and provided the phenomenon with a psychological framework. Money illusion became described as a tendency to think in nominal rather than real terms. While the concept was revived as a part of behavioral and New Keynesian economics, the question of its aggregate effects remains as the Keynes' inconsistency have not been resolved until these days.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses